Contextual Contracts for Component-Based Resource Abstraction in a Cloud of HPC Services - Alam, Wagner Al; Junior, Francisco Carvalho (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2019: Anais do XX Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2019.8670, 2019)
The efforts to make cloud computing suitable for the requirements of HPC applications have motivated us to design HPC Shelf, a cloud computing platform of services for building and deploying parallel computing systems for large-scale parallel processing. We introduce Alite, the system of contextual contracts of HPC Shelf, aimed at selecting component implementations according to requirements of applications, features of targeting parallel computing platforms (e.g. clusters), QoS (Quality-of-Service) properties and cost restrictions. It is evaluated through a small-scale case study employing a componentbased framework for matrix-multiplication based on the BLAS library.